الـتـأويـل البعيد الـقريب وأثـرهمـا فـي الـحكـم الأصـولـي (University of Mosul-college of Basic Education, 2011)
البحث يهدف إلى تحديد مفهوم التأويل البعيد والقريب ودراستهما وأثر كل منهما في الحكم الأصولي المراد معرفته في المسائل الفقهية الفرعية وقبول التأويل أو رده في تلك المسائل باعتبار الأدلة التي تستند إليها وترجيحها واعتبار الرأي المرجوح موهوماً بعيدا في تأويله والنظر في عموم أسباب الخلاف وأثرها ، وذكر ضوابط أو شروط التأويل الصحيح .The research aims to define the concept of interpretation , the near and the distant .Also, study the impact of each of them in the fundamentalist rule that one wants to know in subsidiary doctrinal matters accept the interpretation or a response in such matters as the significance of which they are based and weighted, and consider the correct opinion as something imaginative and far in its interpretation .Also, considering the general reasons for the dispute and its impact, and mentioning the disciplines or the conditions of the correct interpretation .